Work stress in Vista Point Technologies Sdn Bhd / Nurul Ain Hamzah - Hamzah, Nurul Ain (Faculty of Business and Management, 2011)
Stress is essential to our growth, change, development, and performance both at work and at home. There have been frequent complaints from Vista Point Technologies Sdn Bhd employee that they have a heavy work load. Besides that, they also have to face pressures from trying to adapt to new restructure in VPT. Some jobs are stressful by definition because they are physically dangerous (such as firefighting or criminal justice), involve matters of life and death (emergency functions), or are psychologically demanding (social work, teaching). But people who stamp metal or crunch numbers can also be subject to stress on the job. While stress is an individualized experience, there are a variety of demands which serve as stressors for groups of individuals. Four major categories of organizational stressors are identified which are role ambiguity, workload, work environment, and interpersonal relationship. A total of 265 questionnaires were distributed among the employee in various departments. The data received from the respondent was be coded and data were analyzed using SPSS (Statistical Package for Social Science) program. this study also found that work overload is one of the factors that increased stress among respondents. Work stress is an inevitable phenomenon and it is exists in all kinds of job. There is no doubt that the employee in Malaysia is stressful as is known from public opinions and the results revealed in the present study.